Complexity and uncertainty in water resource governance in Northwest Cameroon: Reconnoitring the challenges and potential of community-based water resource management. (June 2018) - Tantoh, Henry Bikwibili; Simatele, Danny
Abstract: This paper examines the complexities and uncertainties which exist in water resource management and governance in Northwest Cameroon. Using empirical data collected through participatory research methods with local communities in Ndu, Njinikom and Mbengwi rural districts in Northwest Cameroon, it is shown that management of water resources is challenged by factors such as uncoordinated national development policies, weak institutional frameworks, top-down management approaches to natural resource management, the paternalistic posture of authorities, the inability of water users to promptly and regularly contribute to the operation and maintenance of the water system, as well as the inadequate preservation of watersheds. In contexts like rural Cameroon one of the key ways in which to improve the supply of water for human use, whilst still conserving water resources, is to make it easier for ordinary water users to work with the other stakeholders involved in water management. Clarifying issues of jurisdiction between central and local governments is central to this process of enabling water users to be involved in the management of their own water supplies. Until the full representation and participation of ordinary citizens in policy discussions is achieved, complexity and uncertainty will overshadow the management of water resources.